2012
DOI: 10.3238/arztebl.2012.0803
|View full text |Cite
|
Sign up to set email alerts
|

Non-Specific, Functional, and Somatoform Bodily Complaints

Abstract: A thorough, simultaneous biopsychosocial diagnostic assessment enables the early recognition of non-specific, functional, and somatoform bodily complaints. The appropriate treatment depends on the severity of the condition. Effective treatment requires the patient's active cooperation and the collaboration of all treating health professionals under the overall management of the patient's primary-care physician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
1
34

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(150 citation statements)
references
References 112 publications
(2 reference statements)
0
111
1
34
Order By: Relevance
“…digestive system, cardiovascular system, respiratory system, urinary system). Accordingly, SHS sufferers are typified by impaired quality of life, frequent hospital visits and incurred medical expenses [20,21]. A previous investigation by the current authors found that suboptimal health status was applicable to 65.1% of the surveyed population in Southern China [24], with SHS now a major global public health challenge [20,25,26].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…digestive system, cardiovascular system, respiratory system, urinary system). Accordingly, SHS sufferers are typified by impaired quality of life, frequent hospital visits and incurred medical expenses [20,21]. A previous investigation by the current authors found that suboptimal health status was applicable to 65.1% of the surveyed population in Southern China [24], with SHS now a major global public health challenge [20,25,26].…”
Section: Introductionmentioning
confidence: 85%
“…Accordingly, SHS sufferers are typified by impaired quality of life, frequent hospital visits and incurred medical expenses [20,21]. A previous investigation by the current authors found that suboptimal health status was applicable to 65.1% of the surveyed population in Southern China [24], with SHS now a major global public health challenge [20,25,26]. Current prevention and intervention strategies recommend disease prevention and effective treatment of early-stage illness [27,28].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…1a Rief et al [2008] und Schaefert et al [2012]). Es wird daher gefordert, Interventionen anzubieten, die auf ein besseres Verständnis und eine bessere persönliche Kontrolle der Beschwerden abzielen [Jonsbu et al, 2012] …”
Section: Anwendbarkeit Der Interventionergebnisse Der Analysenunclassified
“…Innovations in this edition of the Guidelines include i.a. emphasis to features of the doctor-patient relationship important in the treatment of somatoform disorders, taking into account also iatrogenic areas [34].…”
Section: Guidelines and Treatment Pathwaysmentioning
confidence: 99%